Boarding School and Economic Change in Modern Islamic Boarding School Nurul Ikhlas, Tanah Datar Regency (1990-2015) - Beti, Leli Indra (Journal of Philology and Historical Review, 2023)
The establishment of the Nurul Ikhlas Modern Islamic Boarding School in Nagari Panyalaian brought changes to the local community's economy. Economic changes can be seen from people's livelihoods from the agricultural to non-agrarian sectors. The condition of society before the existence of Islamic boarding schools was more focused on agriculture and animal husbandry. The Islamic boarding school provides space for the local community to open businesses related to the needs of the students. These new job opportunities can help people fulfill their needs and alleviate economic problems. This article aims to determine the influence of Islamic boarding schools in changing the economy of the Nagari Panyalaian community. This research is historical research which consists of four stages with steps: heuristics, source criticism, synthesis, and writing (historiography). Apart from using archives, this research uses data collected through interviews and observations. The Nurul Ikhlas Modern Islamic Boarding School has sufficient resources and capital to serve as a basis for economic empowerment of the people. With these resources and capital, Islamic boarding schools can carry out various activities oriented towards the economic empowerment of local people.